Effect of Different Mg Contents on the Microstructure and Properties of a New Zn-Mg Alloy - SHEN Yan, WANG Hong-xing, LI Rui-feng, WANG Jiang-xin (Cailiao Baohu)
In order to improve the properties of Zn-based alloys, a new Zn-Mg casting alloy was prepared by alloying technique. The effects of different Mg contents on the microstructure and properties of Zn-Mg casting alloys were investigated. Results showed that with the increase of the content of Mg, the grain structure was refined and the hardness of the alloy was significantly improved. When the Mg content was at 3%(mass fraction, the same below), the friction coefficient curve tended to be gentle, and the friction coefficient of the alloy was reduced to around 0.40. The addition amount of Mg content significantly affected the corrosion resistance of the Zn-Mg alloy, and when the Mg content was at 2%, the corrosion resistance of the alloy was the best.